Effect of π-aromatic spacers on the magnetic properties and slow relaxation of double stranded metallacyclophanes with a LnIII–MII–MII–LnIII (LnIII = GdIII, DyIII, YIII; MII = NiII, CoII) linear topology. (15th September 2019) - Meseguer, Carlos; Palacios, María A.; Mota, Antonio J.; Drahoš, Bohuslav; Brechin, Euan K.; Navarrete, R.; Moreno, Jose M.; Colacio, Enrique
Graphical abstract: New double stranded metallacyclophanes Ln–M–M–Ln (Ln = Gd III, Dy III, Y III ; M = Ni II, Co II ) with linear topology have been reported to exhibit weak ferromagnetic M II –Ln III and weak antiferromagnetic M II –M II couplings. Ni2 Dy2 counterparts show slow relaxation of the magnetization with U eff values that increase in the order of the NiDy magnetic coupling. Abstract: The coordination-driven self-assembly of two polydentate linear Schiff base ligands (either N, N-bis(2-hydroxy-3-methoxy-benzyliden)-1, 4-diaminobenzene, L2, or N, N-bis(2-hydroxy-3-methoxy-benzyliden)-1, 5-diaminonaphthalene, L3) with two transition metal ions (M II = Ni II or Co II ) and two lanthanide ions (Ln III = Gd III or Dy III ) afforded seven linear M2 Ln2 complexes of formula [Ni2 Ln2 (L2)2 (CH3 CN)3 (H2 O)(NO3 )6 ](CH3 CN)2 (H2 O) (Ln III = Gd1 and Dy2 ) and [M2 Ln2 (L3)2 (CH3 CN)4 (NO3 )6 ](CH3 CN) x (M = Ni II, Co II ; Ln = Dy III, Gd III, Y III ; x = 0–4) (3 –7 ). Within the tetranuclear units of these complexes, two ligands coordinate through the N, Ophenoxide donor sets to two M(II) ions, giving rise to M2 metallacycles. In the case of complexes1 –2, the Ni2 -metallacycle contains 14-members, where the Ni II ions are bridged by para-phenylenediimine groups. In complexes3 –7, the M2 -metallacycle consists of 18-members, where the transition metal ions are linked by naphthalenediimine bridging groups. At both sides of these metallacycles, the M II ions are connected to Ln III ions through phenoxido bridging groups. The analysis of the dc and ac magnetic properties of these complexes reveals that: (i) all the compounds exhibit weak ferromagnetic exchange interactions between the M II and Ln III ions through the bis(phenoxido) bridging groups and weak antiferromagnetic M II –M II interactions transmitted by the acenediimine bridging groups; (ii) DFT calculations not only support the nature and magnitude of the magnetic exchange interactions, but also the polarization mechanism for the M II –M II interactions through the acene bridging legends; (iii) the antiferromagnetic interaction for1 is stronger than for3, which can be justified by the longer intermetallic Ni⋯Ni distance and α, α′-substitution for the latter; (iv) complexes2 and4 show slow relaxation of the magnetization below 5 K at zero static magnetic field with U eff / k B values of 19 K and 15.9 K respectively, the higher U eff / k B value corresponding to the stronger J DyGd coupling constant; (v) the change of −Δ S m for the M2 Gd2 complexes1, 3 and6 has been analyzed by taking into account the values of their J and J 1 magnetic exchange interactions and single-ion anisotropies.